Phytoplankton Composition in Waters Around Hot Water Waste of Steam Electricity Power Plant Nii Tanasa - Arielta, Muhammad Rafly; Kasim, Ma'ruf; S., Salwiyah (Jurnal Biologi Tropis, 2024)
Understanding the complex dynamics of aquatic ecosystems is very important for sustainable resource management in the field of aquatic resource management studies. This study aims to determine the distribution, abundance and diversity of phytoplankton and its correlation with water temperature around the PLTU Nii Tanasa area. The sampling method used is purposive sampling by taking water samples using a plankton net at predetermined stations. Data analysis of abundance, diversity, dominance, and correlation using Microsoft excel software. The number of samples found was 12 types of phytoplankton and came from several different classes. Abundance index (N) = low-moderate fertility (low enough), diversity index (H) = moderate category, dominance (C) = low, indicating stable community structure conditions. Water quality is classified as waters with moderate levels of pollution. Correlation of abundance, diversity and dominance of phytoplankton with water temperature has a positive and negative linear relationship.